THE INFLUENCE OF ENTREPRENEURIAL SKILLS AND MOTIVATION ON ENTREPRENEURIAL INTEREST - Trisnawaty Harefa, Poppi; Kurniawati, Rohmah (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2024)
The problem of this research is the open unemployment rate which is increasing every year. This type of research is quantitative. The data collection technique in this research is multiple regression analysis. By using data collection techniques by means of questionnaires and documentation. before researching the questionnaire, validity and reliability tests were carried out using the help of the SPSS application. And with a research population of 44 students. After collecting the data, the classical assumption test was carried out. From the results of data analysis, it can be seen that the coefficient of determination (R2) is 0.783 or 78.3%. Thus, this value means that the variable Entrepreneurial Skills (X1) and Entrepreneurial Motivation (X2) contributes 78.3% pengaruah to Entrepreneurial Interest (Y) while the remaining 21.7% is influenced by other variables outside the study. From the results of research that has been done shows that there is an influence of entrepreneurial skills and entrepreneurial motivation on entrepreneurial interest, it can be concluded that the more skills possessed and driven by high motivation, the greater the chance of creating a successful business.